THE IMPLEMENTATION OF LEGAL POLITICS IN RELATION TO THE GOVERNMENT'S FUNCTION IN DETERMINING WORKER'S WAGES IN THE PERSPECTIVE OF THE PRINCIPLE OF JUSTICE AND THE PRINCIPLE OF LEGAL CERTAINTY - Wiwi Yuhaeni; Sri Dewi Sartika (Lembaga Penelitian Universitas Pasundan, 2020)
Wage system need to be developed by taking into account the balance between work performance or productivity, workers needs and company capabilities. The formulations of the problem, how the implementation of the legal politics related to the functions of government in the aplication of workers wages in the perspective of the principles of justice and the principle of justice and the principle of legal certainty. Research methods using normative judicial methods and analytical descriptive approaches and analyzed qualitatively. The conclusion is the based on Law Number 13 of 2003 Concerning Emploiment, that income that meets a decent income is intended for workers and their families, whereas in The Minister of Labor and Transmigration on Regulation Number-PER- 13/MEN/VII/2012, the need for a decent living is only intended only for workers or single workers.